(untitled) (Swansea, UK, 1997)
This is reflected in part by the number of papers dealing with fundamental aspects of heat transfer, although, once again, papers dealing with solution of problems of scientific and industrial relevance form a significant, as well as, conduction, convection and radiation,...
Keywords: Heat transfer,Sự truyền nhiệt; Analysis,Numerical methods,Phân tích,Phương pháp số học